2015
DOI: 10.5152/iao.2015.1341
|View full text |Cite
|
Sign up to set email alerts
|

Bonebridge Implantation for Conductive Hearing Loss in a Patient with Oval Window Atresia

Abstract: The occurrence of oval window atresia is a rare anomaly with conductive hearing loss. Traditional atresia surgeries involve challenging surgical techniques with risks of irreversible inner ear damage. Recent reports on Bonebridge (Medel, Innsbruck, Austria), a novel implantable bone conduction hearing aid system, assert that the device is safe and effective for conductive hearing loss. We present a case of Bonebridge implantation in an eight-year-old girl with bilateral oval window atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The preoperative and postoperative results can be seen in the S2 Table. Speech understanding in quiet was assessed in 27 publications [16, 26, 27, 7, 28, 22, 29, 24, 30, 10, 31, 25, 3234, 18, 12, 13, 35, 36, 20, 14, 37, 38, 21, 39], resulting in a mean unaided WRS score of 25.73±23.64% improving to 84.48±15.09% in the aided condition, resulting in an overall mean improvement of almost 60% (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative and postoperative results can be seen in the S2 Table. Speech understanding in quiet was assessed in 27 publications [16, 26, 27, 7, 28, 22, 29, 24, 30, 10, 31, 25, 3234, 18, 12, 13, 35, 36, 20, 14, 37, 38, 21, 39], resulting in a mean unaided WRS score of 25.73±23.64% improving to 84.48±15.09% in the aided condition, resulting in an overall mean improvement of almost 60% (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Safety of the device was assessed by collecting information on complications during surgery and adverse events in the postoperative period (S4 and S5 Tables). Twenty-five [16, 26, 27, 6, 7, 29, 24, 30, 810, 31, 11, 25, 17, 33, 18, 13, 35, 36, 14, 38, 15, 21, 46] publications out of the 39 identified citations reported on complications and adverse events, out of which ten citations (n = 259; 90.6%), explicitly stated that no complications occurred during the full study period [16, 27, 30, 10, 31, 11, 25, 38, 15, 21]. A total of 286 ears were evaluated for safety outcomes over a mean follow-up period of 11.7±4.5 months (range: 3–36 months).…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Kim described a case of bilateral oval window atresia but without atresia of the external auditory canal or microtia in an 8-year-old girl who received a Bonebridge bone conduction implant (BCI) system, which resulted significantly improved hearing [ 26 ]. This previous report confirms the long-term outcomes in cases with congenital ossicular anomalies, where the auditory ossicle system is not functioning, treated with Bonebridge BCI [ 26 ]. The safety and efficacy of the Bonebridge BCI system were initially addressed in a European multicenter study [ 2 , 28 ], and subsequently also demonstrated in children [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noise-induced hearing loss (NIHL) is one of the most common chronic hearing problems, which affects approximately 29 million Americans (9,10). The pathophysiology of NIHL includes a combination of mechanical and metabolic factors.…”
Section: Introductionmentioning
confidence: 99%